Anabolic steroids in myelodysplastic syndromes: A systematic review. (July 2020) - Garcia-Horton, Alejandro; Valliere, Yashoda; Lazo-Langner, Alejandro
Highlights: Anabolic steroids such as danazol are widely used in the treatment of MDS. We conducted a systematic review to assess the evidence for their use. Study design was variable and the results indicated mixed outcomes. Risk-of-bias and study quality tools demonstrated that most studies were flawed. Danazol remains acceptable in low-risk MDS, but randomized trials are needed.